YOUTUBE AS A MEDIA EXPRESSION OF TRANSGENDER WOMEN - Vidya Kusumawardani; Nobertus Ribut Santoso; Dewi Maria Herawati (ASPIKOM Jabodetabek Region, 2020)
YouTube becomes an alternative media to represent homosexual identity that is not portrayed by mainstream media. Dinda Syarief, one of transgender women, uses this platform to express herself as a transgender woman. This research investigates 32 YouTube videos uploaded on her YouTube channel by using content analysis from May 2019 to March 2020. The study reveals that based on the themes, the YouTube videos mostly discussed about her photoshoot activities, apartment tours, truths and dares about Dinda Syarief, modelling, her achievement to be the third winner of Miss International Queen in Thailand and make-up tutorial. Based on transgender-specific issues, disclosure becomes the issue mostly discussed in her videos such as the transition from male to female, surgery, and family reaction after she became a transgender woman. Meanwhile, based on the physical transition, hormones, surgery, voice, and non-surgical procedures become the issues mostly discussed.